FRI0326 Recommendations for the management of neuro-behÇet disease by japanese research committee for behÇet disease. (15th June 2017) - Kikuchi, H; Sawada, T; Okada, M; Takeno, M; Kuwana, M; Ishigatsubo, Y; Kawachi, I; Mochizuki, H; Kusunoki, S; Hirohata, S
Abstract : Background: Central nervous system involvement is one of the most serious complications in Behçet's disease (BD). This condition is referred to as neuro-Behçet's disease (NB) and can be classified into acute type (ANB) and chronic progressive type (CPNB) based upon differences in the clinical course and responses to corticosteroid treatment. Diagnostic criteria were generated in 2013 based on a multicenter clinical survey performed by the Behçet's Disease Research Committee of the Ministry of Health, Labor and Welfare of the Japanese Government. Although "Guidelines for Treatment of NB" was also proposed based on the survey, it is still preliminary. Objectives: The aim of the current study is to develop evidence-based recommendations for the management of NB supplemented by expert opinions where necessary. Methods: First, clinical questions (CQs) on NB were extracted from a literature search for problem areas and related keywords, and draft CQs and a flow chart were prepared. The expert committee, a task force of the research subcommittee for NB, consisted of 7 board-certified rheumatologists (one was also a board-certified neurologist) and 3 board-certified neurologists. A systematic literature search was performed using Medline and the Japan Medical Abstract Society databases from 1997 to 2016. A total of 15 initial CQs were generated. These yielded the final recommendations developed from 3 blind Delphi rounds, in which the rate of agreement scores on CQs (range 1 [disagree]–5 [strongly agree]) was determined though voting by the whole committee. Results: Thirteen recommendations were developed for the management of NB (general 1, ANB 7, CPNB 5). The strength of each recommendation was established based on the evidence level as well as rate of agreement. There was excellent concordance between the level of agreement of rheumatologists and that of neurologists. Based on these recommendations, a flow chart was established for the management for ANB and CPNB (Figure). Conclusions: The recommendations generated in this study are mainly based not only on expert opinions but on the results of uncontrolled evidence from open trials and retrospective cohort studies. Guidelines that can be used for international studies are needed, for which verification by further properly designed controlled clinical trials is required. Disclosure of Interest: None declared